Taste disorders after tonsillectomy: a long-term follow-up - Heiser, Clemens; Hörmann, Karl; Stuck, Boris (The laryngoscope, 2012)
In a former study, taste disturbances after tonsillectomy seemed to be more frequent than expected. Eight percent of patients reported subjective taste disorders 6 months after tonsillectomy. Fifteen patients from the initial trial, who reported taste disorders after tonsillectomy, were contacted again for this long-term follow-up. A telephone interview using the same questionnaire addressing the current self-estimate of taste function was performed. At 32 ± 10 months following surgery, two (0.9%) patients still reported suffering from taste disturbance. This long-term follow-up study shows that dysgeusia following tonsillectomy occurs in approximately 1% of patients. These data should be considered when patients are informed about complications after tonsillectomy.